2017
DOI: 10.1080/14615517.2017.1364019
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effectiveness of mandatory integration of health impact assessment within environmental impact assessment (EIA): a case study of Thailand

Abstract: The effectiveness of the integration of health impact assessment (HIA) and environmental impact assessment (creating an environmental and health impact assessment’ (EHIA) process) is investigated, drawing on an example of a mandatory requirement in the power plant project sector in Thailand. The analytical framework is based on that outlined in by the authors in 2013, focusing on procedural, substantive, transactive and normative effectiveness criteria, and the evaluation served also to critique this framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Past experience with EIA shows that policy makers struggle to satisfy policy goals including political, economic and social aims, are challenged to find ways for enforcing EIA recommendations, and that governments are concerned about how to integrate different policy initiatives [ 46 , 47 ]. Stakeholders from Port Louis highlight similar issues.…”
Section: Resultsmentioning
confidence: 99%
“…Past experience with EIA shows that policy makers struggle to satisfy policy goals including political, economic and social aims, are challenged to find ways for enforcing EIA recommendations, and that governments are concerned about how to integrate different policy initiatives [ 46 , 47 ]. Stakeholders from Port Louis highlight similar issues.…”
Section: Resultsmentioning
confidence: 99%
“…This research was conducted using a qualitative approach involving literature review, encompassing reviews of legislation, guidance documents, Government reports and past evaluations (related to IA practice in Thailand, which have been published as presented in Table 1, (for example, Baird andFrankel 2015, Wangwongwattana et al 2015)). The past evaluations encompass data collections based on documentary analysis for measuring SEA effectiveness (Chanchitpricha et al 2019) and documentary analysis coupled with stakeholder interviews for investigating the effectiveness of HIA and environmental and health impact assessment (EHIA) (Chanchitpricha 2012, Chanchitpricha and Bond 2018, Fakkum 2013, Wangwongwattana et al 2015. (Chanchitpricha, Morrison-Saunders andBond 2019, Wirutskulshai et al 2011) In order to reflect on past practice, in this paper, we examined the effectiveness of Thai IA practice based on the recent conceptualisations of effectiveness (Chanchitpricha et al 2019), associated with a timeline of the evolution of Thai practice.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was highlighted that guidelines on IA practice and public participation in the IA process should be clear and appropriate to apply in real practice (e.g. Chanchitpricha and Bond 2018). Montaño and Fischer (2019) argued that the 'institutional and normative context' can't be overlooked in providing upto-date guidance for SEA / IA practice to help improve its effectiveness.…”
Section: History Of the Impact Assessment (Ia) System In Thailandmentioning
confidence: 99%
See 1 more Smart Citation
“…EIA as policy tools also empowers the government to prosecute environmental offences in the law courts. However, experience with EIA has shown that government institutions in both industrialised and developing countries often lack the capacity to evaluate the quality of the assessments and are facing challenges in monitoring and enforcement (Morrison-Saunders et al 2012;Zvijakova et al 2014;Chanchitpricha and Bond 2018;Hacon et al 2018).…”
Section: Impact Assessmentmentioning
confidence: 99%